2015
DOI: 10.1080/15226514.2015.1109603
|View full text |Cite
|
Sign up to set email alerts
|

Copper uptake byPteris melanocaulonFée from a Copper-Gold mine in Surigao del Norte, Philippines

Abstract: The ability of some plants to take up metal contaminants in the soil has been of increasing interest as an environmental approach to pollution clean-up. This study aimed to assess the ability of Pteris melanocaulon for copper(Cu) uptake by determining the Cu levels in the fern vis-à-vis surrounding soil and the location of Cu accumulation within its biomass. It also aimed to add information to existing literature as P. melanocaulon are found to be less documented compared to other fern metal accumulators, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The accumulation capability of Pityrogramma calomelanos is 1,505 µg/g in the root part and 151 µg/g in the shoot part (De la Torre et al, 2015). As for the study conducted by Dahilan and Dalagan (2017) they reported that the uptake of Cu in the belowground tissue of Pityrogramma calomelanos ranges from 262 µg/g to 6,883.32 µg/g.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The accumulation capability of Pityrogramma calomelanos is 1,505 µg/g in the root part and 151 µg/g in the shoot part (De la Torre et al, 2015). As for the study conducted by Dahilan and Dalagan (2017) they reported that the uptake of Cu in the belowground tissue of Pityrogramma calomelanos ranges from 262 µg/g to 6,883.32 µg/g.…”
Section: Introductionmentioning
confidence: 82%
“…As for the study conducted by Dahilan and Dalagan (2017) they reported that the uptake of Cu in the belowground tissue of Pityrogramma calomelanos ranges from 262 µg/g to 6,883.32 µg/g. Another species of fern found out to accumulate copper is Pteris melanocaulon that have been studied by De la Torre et al (2015). This species can accumulate high concentrations of copper in the root but in contrast to Pteris vittata and Pteris melanocaulon there is a shortage of documentation on the metal accumulation potential of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that heavy metal accumulation level and tissue distribution determines what phytoremediation technique (e.g., phytoextraction or phytostabilization) the plant is suitable for. Plants that accumulate high heavy metal concentrations in roots could be designed as phytostabilizers, whereas several species are still recommended as phytoextractors ( De la Torre et al., 2016 , Asensio et al., 2018 , Manzoor et al., 2018 , Eisazadeh et al., 2019 ). For example, chive is designated as a potential species for reducing Cd from contaminated soils despite the low Cd reallocation from roots to shoots ( Eisazadeh et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, chive is designated as a potential species for reducing Cd from contaminated soils despite the low Cd reallocation from roots to shoots ( Eisazadeh et al., 2019 ). By contrast, Pteris melanocaulon , which exhibits a high Cu BCF of 4.04 and a low Cu TF of 0.01, has potential as a metallophyte for Cu phytostabilization ( De la Torre et al., 2016 ). In the present study, the significantly high Cd concentrations in the roots and low TFs of the three S. trifasciata cultivars indicate that these plants are more suitable for phytostabilization, although approximately 1/2 of the total Cd was allocated in the shoots.…”
Section: Resultsmentioning
confidence: 99%
“…Transfer and accumulation of metals from soil to plants is complex and often site-specific. Factors influencing this include: the chemical forms of the heavy metal; the pH of the soil; the soil organic matter content; soil nutrient contents; root exudation of organic acids and flavonoids; soil texture (particularly clay content); mycorrhizal symbiosis, microbial activity and abundance; the plant species; the plants stage of growth; climatic conditions and irrigation with polluted waters (Aladesanmi et al, 2019;Claveria et al, 2019b;Dahilan and Dalagan, 2017;de la Torre et al, 2016;De Oliveira et al, 2020;Domingo and David, 2014;Feigl et al, 2020;Mahajan et al, 2016;Navarrete et al, 2017;Sanqui et al, 2020;Susaya et al, 2010;Tibbett et al, 2021;Yashim et al, 2014).…”
Section: Metal Partitioning and Phytoextraction/phytomining Potentialmentioning
confidence: 99%